Endogenous avidin-binding activity in human lymphoid tissue. Issue 2 (February 1984) - Banerjee, D; Pettit, S
Abstract : Biotin-avidin systems can be used as an alternative to indirect antibody sandwich methods in the detection of T lymphocyte subsets in cryostat sections of human lymphoid tissue. Appreciable endogenous avidin binding activity (EABA) has been found, however, in human lymph nodes and tonsils. Such EABA can be a source of false positive staining when biotin-avidin detection systems are used to identify cells in cryostat sections. The finding that avidin binding cells may also contain endogenous peroxidase activity and are morphologically similar to histiocytes suggests that such cells may be of histiocytic lineage. EABA is not seen in intrafollicular "tingible body" macrophages, however, and only rarely in medullary sinus histiocytes. Thus further studies are necessary to identify the lineage of avidin binding cells in lymphoid tissues. EABA can be effectively blocked by treatment of cryostat sections with 1% avidin followed by 0.01% biotin before specific staining with biotinylated antibodies and avidin-peroxidase or avidin-fluorochrome conjugates.